Analisa Tegangan-Regangan Struktur Pegas Daun Akibat Modifikasi Penekanan - Ismail Thamrin (Universitas Sriwijaya, 2009)
Leaf spring represent one of suspension systems found on vehicle, and functioning as vibration silencer, at the same time as vehicle construct. Effect of modification by pressing, leaf spring function accepting a repeating dynamic load, will experience of damage effect of fatigue which emerge after the component experience its function. Intention of this research is to analysis effective stress - strain that happened at leaf spring structure effect of pressing modification. From result of stress analysis, in the leaf spring which have natural pressing, have an increasing of maximum stress, that is from 1.09361 x 108 N/m2 become 1.12632 x 108 N/m2, or haveÂ degradation of strength equal to 3%. This matter can cause possibility to the happening of broken at leaf spring after pressed is bigger comparing to before pressed.